Profilaxia do tromboembolismo venoso nas cirurgias ortopédicas - Roberto Zambelli de Almeida Pinto (2022)
Deep vein thrombosis (DVT) and pulmonary embolism are the main clinical manifestations of venous thromboembolism (VTE). VTE is a common and potentially serious complication of orthopedic surgeries, as it can lead to functional limitation and postoperative death. The use of thromboprophylaxis markedly reduces the incidence of VTE related to orthopedic interventions, and its use is recommended by several guidelines. However, the indication and type of thromboprophylaxis for some orthopedic interventions, as well as the use of risk prediction tools are still not well established and is debatable. The objectives of this study were to identify risk factors for VTE and their interactions in orthopedic surgeries and to evaluate the applicability of the Caprini risk score in predicting VTE in orthopedic patients. In addition, due to the lack of knowledge and recommendations on thromboprophylaxis in foot and ankle surgeries, a narrative review and an international survey on the subject were carried out. Data from the MEGA Study (Multiple Environmental and Genetic Assessment of risk factors for venous thrombosis) which is a Dutch population-based case-control study whose outcome of interest is VTE were used. A total of 263 subjects who had VTE and 94 controls underwent orthopedic surgery. The risk of VTE was the highest in the first 30 days after surgery (adjusted odds ratio [ORadj] 17.5; 95% CI [confidence interval], 9.2-33.4) and remained increased up to 90 days (ORadj, 11.5; 95% CI, 7.3- 17.7). There was interaction between orthopedic surgery and factor V Leiden mutation (ORadj 17.5, 95%CI 4.1-73.6), non-O blood type (ORadj 11.2; 95%CI 3.4-34.0) and factor VIII plasma levels greater than 150 mg/dl (ORadj 18.6; CI 7.4-46.9). To assess the applicability of the Caprini Score, 357 individuals with VTE undergoing orthopedic surgery in the MEGA were evaluated. A total of 20.9% of cases and 41.5% of controls were classified in the lowest risk group (Caprini <5 points). Patients with a Caprini score greater than 11 points had a six-fold increased risk of VTE (OR 6.3, 95% CI 1.7- 22.9) and patients with a score of 9-10 had about three-fold increased risk (OR 3.5, 95% CI 1.2-10.3). The area under curve for the Caprini score was 0.64, evidencing a moderate VTE prediction discrimination. In the international survey on foot and ankle thromboprophylaxis, 693 orthopedic foot and ankle surgeons from 49 countries participated. Approximately 50% reported prescribing thromboprophylaxis during patient immobilization that, when used, the preferred choice, in descending order, was acetylsalicylic acid (ASA), low molecular weight heparin (LMWH) and direct oral anticoagulants. ASA and LMWH were predominantly prescribed in North America and Europe, respectively. Previous DVT, immobility, obesity and hereditary thrombophilia were considered the main risk factors indicative of the use of thromboprophylaxis. It is concluded that there was increased risk of VTE and interaction between factor V Leiden, high plasma levels of factor VIII or non-O blood group and orthopedic surgery; that the Caprini score is a tool that can help orthopedic surgeons to classify the risk of postoperative VTE, although its discriminative predictive performance was moderate and that although most ankle and foot orthopedic surgeons consider that thromboprophylaxis is indicated for ankle and foot surgeries (especially in the presence of risk factors such as previous DVT, immobility, obesity and hereditary thrombophilia), the prescription, type and duration present a large intercontinental discrepancy. Thus, this work contributed to the identification of patients at high risk of VTE, a strategic point for the individualized and safe use of thromboprophylaxis as a tool to reduce the risk of VTE related to orthopedic surgeries.